Amok - Eisler, Barry (Thomas & Mercer, 2022)
"1991. A restless young man called Dox is back home in Texas. His friends have missed him, and his mother and sisters need him. But after four years as a Marine and another two as a CIA contractor fighting the Soviet Union alongside the Afghan mujahideen, small-town life in Abilene is a suffocating dead end. Another secret war, this one in Southeast Asia, offers a big payday and the solution to his family's troubles. But secret wars are never what they're billed to be, and Dox is about to get the education of his young life. Among the lessons--the only thing more dangerous than war is falling in love with your enemy."--